Routinely available biomarkers improve prediction of long-term mortality in stable coronary artery disease: the Vienna and Ludwigshafen Coronary Artery Disease (VILCAD) risk score - Goliasch, Georg; Kleber, Marcus E.; Grammer, Tanja B.; März, Winfried (European heart journal, 2012)
AbstractAims. Previous risk assessment scores for patients with coronary artery disease (CAD) have focused on primary prevention and patients with acute corona